Phygital Marketing Transformation: Integrating QRIS to Enhance Customer Experience and Engagement - Dodhy Hyronimus Ama Longgy; Florentina Blandina Parapaga; Yumiad Fernando Richard; Jacobus Rico Kuntag (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Digital transformation drives the convergence between physical and digital spaces in retail marketing, known as phygital marketing. In Indonesia, the Quick Response Code Indonesian Standard (QRIS) has become a key instrument in supporting technology-based customer experiences. This study aims to examine the influence of perceived information quality, system quality, service quality, transaction speed, and risk on customer experience and customer engagement in the use of QRIS. Using an explanatory sequential mixed-method design, the quantitative phase involved 188 QRIS users in traditional retail, followed by in- depth interviews with five business actors in Merauke Regency. Data analysis using SEM- PLS showed that perceptions of information, system, and service quality had a positive effect on customer experience, while perceived risk had a negative effect. However, transaction speed had no significant effect. Only customer experience directly influenced customer engagement and partially mediated most of the indirect effects of the perceptual variables. Qualitative findings confirmed that business actors faced challenges related to infrastructure, technological understanding, and support services, which affected the optimal use of QRIS. This study extends the ISSM model by incorporating risk and transaction speed dimensions and emphasizes the importance of customer experience in strengthening user engagement. Practical implications include the need for education, technical support services, and enhancement of digital infrastructure to increase the sustainable adoption of QRIS in the traditional retail sector.